Estado da Prática do Design Visual de Aplicativos Móveis desenvolvidos com App Inventor - Solecki, Igor da Silva (2023)
App Inventor is a blocks-based programming environment that allows any end-user to create mobile applications. It is frequently used in order to teach computing in K-12 through the development of mobile apps. Although learning computing with App Inventor has been investigated from different points of view, a question that remains is whether the visual design of the user interfaces (UI) of the applications developed with App Inventor is adequate, being one of the major success factors of a mobile application. Therefore, this article analyzes the visual design of the user interfaces of 88,861 apps from the App Inventor gallery in relation to its compliance with style guides through an automated source code analysis, as well as its aesthetics based on a survey with 95 participants assessing 110 UIs. The results show that most UIs do not comply to design guidelines and do not have visual aesthetics. Therefore, it seems important to cover not only programming concepts, but also UI design in computing education when developing mobile applications. The results of this analysis can drive the development and improvement of instructional units and the App Inventor environment, thus contributing to the development of applications with better UI design and increasing their chances of having success.